PENGARUH CASH HOLDING, PROFITABILITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP INCOME SMOOTHING - Boen, Angellia; Bangun, Nurainun (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to analyze the factors that influence income smoothing in manufacturing companies listed on the Indonesia Stock Exchange during the period of 3 years (2018-2020). The sampling method used in this research is purposive sampling. The final sample used in this study amounted to 31 manufacturing companies. The analysis used in this study is logistic regression. The data that has been collected is processed using Eviews version 12 software. The results show that the independent variable cash holding and managerial ownership have a positive and insignificant effect on the dependent variable (income smoothing), and the independent variable profitability has a negative effect on the dependent variable (income smoothing).